Investigation of the impact of a broad range of temperatures on the physiological and transcriptional profiles of Zymomonas mobilis ZM4 for high-temperature-tolerant recombinant strain development - Runxia Li; Wei Shen; Yongfu Yang; Jun Du; Mian Li; Shihui Yang (Biotechnology for Biofuels, 2021)
Abstract The model ethanologenic bacterium Zymomonas mobilis has many advantages for diverse biochemical production. Although the impact of temperature especially high temperature on the growth and ethanol production of Z. mobilis has been reported, the transcriptional profiles of Z. mobilis grown at different temperatures have not been systematically investigated. In this study, Z. mobilis wild-type strain ZM4 was used to study the effect of a broad range of temperatures of 24, 30, 36, 40, and 45 °C on cell growth and morphology, glucose utilization and ethanol production, as well as the corresponding global gene expression profiles using RNA-Seq-based transcriptomics. In addition, a recombinant Z. mobilis strain expressing reporter gene EGFP (ZM4_EGFP) was constructed to study the effect of temperature on heterologous protein expression at different temperatures. Our result demonstrated that the effect of temperature on the growth and morphology of ZM4 and ZM4_EGFP were similar. The biomass of these two strains decreased along with the temperature increase, and an optimal temperature range is needed for efficient glucose utilization and ethanol production. Temperatures lower or higher than normal temperature investigated in this work was not favorable for the glucose utilization and ethanol production as well as the expression of exogenous protein EGFP based on the results of flow cytometry and Western blot. Temperature also affected the transcriptional profiles of Z. mobilis especially under high temperature. Compared with ZM4 cultured at 30 °C, 478 genes were up-regulated and 481 genes were down-regulated at 45 °C. The number of differentially expressed genes of ZM4 cultured at other temperatures (24, 36 or 40 °C) was relatively small though compared with those at 30 °C. Since temperature usually increases during the fermentation process, and heat tolerance is one of the important robustness traits of industrial strains, candidate genes related to heat resistance based on our RNA-Seq result and literature report were then selected for genetics study using the strategies of plasmid overexpression of candidate gene or replacement of the native promoter of candidate gene by an inducible P tet promoter. The genetics studies indicated that ZMO0236, ZMO1335, ZMO0994, operon groESL, and cspL, which encodes Mrp family chromosome partitioning ATPase, flavoprotein WrbA, an uncharacterized protein, chaperonin Cpn10 and GroEL, and an exogenous cold shock protein, respectively, were associated with heat tolerance, and recombinant strains over-expressing these genes can improve their heat tolerance. Our work thus not only explored the effects of temperature on the expression of exogenous gene EGFP and endogenous genes, but also selected and confirmed several genes associated with heat tolerance in Z. mobilis, which provided a guidance on identifying candidate genes associated with phenotypic improvement through systems biology strategy and genetics studies for other microorganisms.